Community Participation in Two Vaccination Trials in Slums of Kolkata, India: A Multi-level Analysis (Journal of Health, Population and Nutrition, 2010)
This study aims at understanding the individual and community-level characteristics that influenced participation in two consecutive vaccine trials (typhoid and cholera) in urban slums of Kolkata, India. The study area was divided into 80 geographic clusters (communities), with 59,533 subjects aged ≥2 years for analysis. A multi-level model was employed in which the individuals were seen nested within the cluster. Rates of participation in both the trials were nearly the same; those who participated in the initial trial were likely to participate in the subsequent cholera vaccine trial. Communities with predominantly Hindu population, lower percentage of households with an educated household head, or lower percentage of households owning a motorbike had higher participation than their counterparts. At individual scale, higher participation was observed among younger subjects, females, and individuals from households with a household head who had no or minimal education. Geographic patterns were also observed in participation in the trials. The results illustrated that participation in the trial was mostly influenced by various individual and community-level factors, which need to be addressed for a successful vaccination campaign. Key words: Cholera; Cholera vaccines; Typhoid fever; Typhoid-paratyphoid vaccines; Vaccination; India DOI: 10.3329/jhpn.v28i5.6153 J HEALTH POPUL NUTR 2010 Oct;28(5):450-457